A solvent-free in situ synthesis of a hierarchical Co-based zeolite catalyst and its application to tuning Fischer–Tropsch product selectivity. Issue 11 (9th May 2018) - Mazonde, Brighton; Cheng, Shilin; Zhang, Guihua; Javed, Mudassar; Gao, Weizhe; Zhang, Yu; Tao, Meng; Lu, Chengxue; Xing, Chuang
Abstract : As a distinctive supportable route, the solvent-free synthesis of zeolites not only minimizes the problems of conversional hydrothermal synthesis, but also greatly increases the product yields with advantageous characteristics, such as reduced waste production and a hierarchical pore structure. Abstract : As a distinctive supportable route, the solvent-free synthesis of zeolites not only minimizes the problems of conversional hydrothermal synthesis, but also greatly increases the product yields with advantageous characteristics, such as reduced waste production and a hierarchical pore structure. Herein, we demonstrate using in situ crystal Co/SiO2 to form a hierarchical catalyst with Co particles entrapped inside the ZSM-5 body via a solvent-free process. Na-type zeolite catalysts enhanced the production of gasoline-range (C5 –C11 ) products, with Co@NaZSM-5 giving a high selectivity of 68% in the Fischer–Tropsch synthesis. Obviously, all characterizations showed that these solvent-free synthesized samples had high crystallization and a high surface area for mass transfer. This hierarchical zeolite has the potential to be applied to other similar materials owing to its convenient synthesis method, features, and outstanding results.